Organizational continuity and change of chinese business organizations in Singapore - Cheng, Eugene Chee Mun (2008)
The objective of this research is to study the persistence and change of the organizational and business strategies of Chinese business organizations (CBOs). In this research, we propose that while Chinese business organization (CBOs) expand, they are likely to maintain family ownership and control, while changing in terms of their management and networking strategies.